Determination of acrylamide in fried food product by matrix solid dispersion with ultra-high performance liquid chromatography-tandem mass spectrometry - Lapviboonsuk, Jutathip; Lapviboonsuk, Sompop (Bulletin of Applied Sciences, 2022)
The determination of acrylamide in fried food products was studied the suitability of liquid chromatography – tandem mass spectrometry and also performed sample preparation technique: matrix solid dispersion or QuEChERS. The method validation was performed and fell in acceptable range as following the EU Commission regulation 2017/2158. The averages of recoveries were 100.7, 95.3 and 103.8 % at the concentration level of 20, 500 and 1,000 g kg-1, respectively. The precision was also in the acceptable range. The relative standard deviations (RSDs) were in the range of 3.82% - 8.00%. Moreover, the detection limit and quantitation limit were 5 and 20 g kg-1, respectively. These results demonstrated that the method was reliable and suitable for the measurement of acrylamide content in fried food products.